Phenolic Acids, Steroids, and Triterpenoids Isolated from Platycodon grandiflorus (Jacq.) A. DC. - Huu Giap, Tran; Thi Tu Oanh, Nguyen; Xuan Nhiem, Nguyen; Van Hung, Nguyen; Mai Thao, Vu; Thi Thoa, Ha; Phuoc Hoa, Bui; Thi Minh Hang, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 1DO - 10.25073/2588-1132/vnumps.4558, 2024)
Platycodon grandiflorus (Jacq.) A. DC. is a precious medicinal plant, which is one of 54 medicinal species selected by the Vietnamese government for development in specialized areas of medicinal herbs. Currently, P. grandiflorus has been planted in some regions in Vietnam. Although P. grandiflorus has been commonly used in traditional Vietnamese medicine, the reports on the chemical composition and biological activity of this plant are limited in our country. As a part of our research on the hypolipidemic effect of P. grandiflorus , six compounds including ferulic acid ( 1 ), caffeic acid ( 2 ), p -hydroxy benzoic acid ( 3 ), spinasterol ( 4 ), sitostenone ( 5 ), and betulin ( 6 ) were isolated from the ethyl acetate and n -hexane extracts of the roots of P. grandiflorus . The structures of these compounds were determined based on NMR and MS spectral data and comparison with those reported in the literature. Compound 5 has been found in P. grandiflorus for the first time.